Fluorescence imaging in the surgical management of liver cancers: Current status and future perspectives - Qingliang Wang; Xiaojie Li; Baifeng Qian; Kunpeng Hu; Bo Liu (Asian Journal of Surgery, 2022)
Over the last decades, imaging technologies have got significant developments and become indispensable in the surgical management of liver cancers. Real-time navigation afforded by intraoperative images has a significant impact on the success of liver surgeries. Fluorescence imaging in the near-infrared spectrum has shown potential for tumor detection and image-guided surgery in clinics. While predominantly focused on indocyanine green (ICG) imaging, there is also accelerated development of more specific molecular tracers. Compared to passive targeting contrast agents ICG, active targeting and activatable probes both shed new light for intraoperative navigation owing to the higher degree of specificity for the tumor target. A variety of fluorescence imaging probes have been developed to target biomarkers unique to cancer cells or tumor microenvironment and demonstrated promising results. In this review, we provide a comprehensive update on preclinical development and clinical applications of fluorescence imaging in the surgical management of liver cancers. By highlighting the current status, we aim to offer insight into the challenges and opportunities for further investigation.